La oferta turística y la comercialización de las artesanías tradicionales en la ciudad de Riobamba - Vega Bonilla, Roberto Carlos (2019)
The crafts are miniature sculptures made with materials such as wood, tagua, leaf of com, glass, metal etc., which expresses the culture and tradition of Riobamba city. It preserves its iconography and color. The objective of this research was to develop a diagnosis of traditional handicrafts in the city of Riobamba as part of the tourist offer to improve its commercialization. For achieving this objective, handicraft characterization from Riobamba district was firstly carried out. Additionally, traditional handicrafts are linked to tourist activity, depending the identification of the sector. Thirdly, production determination and traditional handicraft commercialization was finally established by providing a marketing proposal which promotes and disseminates handicrafts. As part of the development of the research, it was necessary to base bibliographical work in order to support arguments about tourist offers, crafts and marketing strategies for an adequate commercialization. The type of research according to its approach was qualitative-quantitative since the gathered data was qualitative and quantitative which respond to the problem statement. Therefore, it allowed identifying handicraft forms and types, elaboration time, costs. The technique was an interview which was addressed to artisan union, specifically to the president. Consequently, future needs and projects were known. The instruments were the interview guide and the tab for the inventory of attractions. For the calculation of the sample, a population of one- hundred-four artisans was employed. The study resulted in eighty-two skilled artisans. The results obtained in the study determined that artisans do not have strategies to improve the commercialization of their products. Finally, it is concluded that it i$ necessary to implement a marketing strategy to improve crafts commercialization on the city. For this reason, a marketing plan was developed based on the product, price, place and promotion to improve the commercialization of traditional handicrafts in the city of Riobamba